VEGETAL RITUAL OFFERINGS FROM A LATE BRONZE AGE PIT FROM VLAHA-PAD SITE, CLUJ COUNTY, ROMANIA - Ciuta Elena Beatrice; Florin GOGÂLTAN (Journal of Ancient History and Archaeology)
An amazing and extremely rare archaeological context discovered at the Vlaha-Pad site located in the Transylvania area (Cluj County, Romania) may be related to offerings in the Late Bronze Age. Radiocarbon calibrated data indicates that the context ranges from 1612 to 1433 cal BC. The context is particularly important regarding the unearthing of a wood barrel full of sprouted barley that can be associated with a ritual offering to Gods. In addition to the wood barrel, several special vessels that are usually related to ritual practices have been uncovered. The archaeological materials recovered from within belong to the Wietenberg IV culture dated to the Late Bronze Age. Our study focuses on the context with ritual deposition and the possible hypotheses related to it.